A importância do brincar na educação infantil: uma análise teórica - Oliveira, Janielle Neves de (Universidade Federal do Rio Grande do Norte, 2018)
The importance of playing in children's education arises through the construction of concepts of children, childhood, early childhood education and play. Thus, the goal of this Arctic is to understand how the act of playing can influence the learning of children and what place it occupies in the routine of children's institutions. The methodological approach is the bibliographic analysis allied to the experiences obtained during the graduation. This article was constructed from the historical re-signification of the concepts of children, infancy and early childhood education that allowed a greater understanding of the role the child occupied in society, especially in the seventeenth and eighteenth centuries and what role it occupies in the current organization. And from this it was possible to understand how the official documents together with other sources highlight the role of play for the development of the child and the responsibility of teachers to organize their routines considering that playing as one of the most important points of education of Together with caring and teaching. Este artigo tem como objetivo e desenvolvimento compreender como o ato de brincar pode influenciar na aprendizagem das crianças e que local ele ocupa na rotina das instituições infantis. Utilizamos como procedimentos metodológicos a análise bibliográfica aliada as experiências obtidas ao longo da graduação. E a partir disso foi possível compreender de que modo os documentos oficiais, juntamente com outras fontes destacam a importância do brincar para o desenvolvimento infantil e a responsabilidade dos professores em organizar suas rotinas considerando que o brincar é de grande relevância na educação da infância juntamente com o cuidar e ensinar. Palavras-chave: Educação Infantil, Brincadeiras, Criança